Characteristic of Noni (Morinda citrifolia Linn) Fruit Juice Produced by Fermentation - Hardoko .; Adolf Parhusip; Ivonne P Kusuma (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Fermentation is one of the methods to get noni juice. In this research, noni is fermented in hanged system and submerged system for 1, 2, 3, and 4 weeks. The result showed the longer fermentation increased pH, alcohol content, turbidity, viscosity, microbial content, and decrease ascorbic acid and acid content, soluble solid content, color and flavor acceptance. Differennt system fermentation affected percent yield, soluble solid content, turbidity of juice, panels opinion to color significantly. Noni juice of submerged system has higher percent yield, higher soluble solid content, turbidity, but provided lighter color than noni juice of hanged system. Juice of submerged system is better than hanged system. Juice from three weeks fermentation indicated changes of metabolism activity which is shown by some characteristic changes. Fruit juice made by submerged fermentation system had more diverse compounds than fruit juice without fermentation. Key words : Noni juice, fermentation.